A detailed lipoprotein profile in relation to intima‐media thickness and echogenicity of three major arteries. (7th October 2019) - Lind, Lars
Summary: Objective: To investigate differences in risk‐factor profile, with special emphasis on detailed characterization of the lipoprotein profile, for intima‐media thickness (IMT) and echogenicity of the intima‐media complex (IM‐GSM) in three major arteries: the carotid, femoral and brachial arteries. Methods: IMT and IM‐GSM were measured by ultrasound in the carotid, femoral and brachial arteries in 778 subjects, all aged 75 years (50% women), in the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) study, in which a detailed lipoprotein profile was also determined by nuclear magnetic resonance spectroscopy. Results: First, IMT was considerably lower, and IM‐GSM higher, in the brachial artery compared to the other two arteries. Second, IMT and IM‐GSM in the arteries were related to each other. Third, significant different traditional risk‐factor profiles were seen for both IMT and IM‐GSM, with generally weaker relationships for IMT in the femoral and brachial arteries compared with the carotid artery. Fourth, the strength of associations between an atherogenic lipoprotein profile and IMT in the carotid artery was attenuated in the femoral artery and virtually absent in the brachial artery. Fifth, slightly different lipoprotein profiles were seen for IM‐GSM in the three arteries. Conclusion: Differences between the carotid, femoral and brachial artery IMT and IM‐GSM were seen regarding the traditional risk factors, as well as the lipoprotein profile.